Features of the use of the antibacterial drug josamycin in gynecological practice - A. Z. Khashukoeva; M. I. Agaeva; Z. A. Agaeva; M. V. Burdenko; L. A. Nosova; I. Z. Khashukoeva (Лечащий Врач)
Background. Currently, urogenital chlamydia occupies the first place in terms of prevalence among all bacterial sexually transmitted diseases. Along with chlamydia, other intracellular pathogens, mycoplasmas and ureaplasmas, are attracting increasing attention in the etiology of urogenital diseases. Inflammatory diseases of the pelvic organs cause significant damage to the health of women, contribute to the violation of reproductive function, reduce the quality of life, as well as the formation of life-threatening conditions in severe course. The issues of timely diagnosis of inflammatory diseases of the reproductive system present many difficulties, justified by the vagueness of clinical symptoms, the variety of causative agents, as well as the different course of the inflammatory process. Neisseria gonorrhoeae, Chlamydia trachomatis, Mycoplasma genitalium, Trichomonas vaginalis are the leading etiologic factors of inflammatory diseases of pelvic organs, up to 60% of cases of inflammatory diseases of female genital organs are the result of microbial associations of Chlamydia trachomatis, Mycoplasma genitalium. These infections are most dangerous during pregnancy. Difficulties in diagnosis lead to delayed treatment, which contributes to an increase in the number of chronic forms of diseases and unfavorable outcomes associated with a complicated course of diseases. Therapy of inflammatory diseases of the genitals requires a comprehensive approach and causes a lot of discussion, the main link of treatment is the rational selection of antibacterial therapy.Results. This review demonstrates current data on the high efficacy and safety of the use of josamycin in the treatment of these diseases. The use of the domestic drug with active substance josamycin in the treatment of inflammatory diseases of the pelvic organs, urogenital chlamydia and mycoplasmosis, especially during pregnancy, is effective and safe, and will reduce the frequency of adverse pregnancy outcomes and infectious and inflammatory complications.